ANALISIS LEKSIKAL KATA “LOGOS” DALAM YOHANES 1:1 - Steyven Tirajoh; Aprianus Moimau (BONAFIDE: Jurnal Teologi dan Pendidikan Kristen, 2026)
ABSTRACT This study examines the lexical meaning of the word Logos in John 1:1 and its Christological implications for the faith of Christians today. The research focuses on the meaning of Logos in the context of the Greek language, its understanding in Christology, and its relevance to the lives of believers. Many Christians understand “Logos” merely as “the Word” without realizing its theological significance as the divine revelation of Christ. This study aims to analyze the lexical meaning of “Logos,” explain its Christological significance, and identify its relevance to the Christian faith today. The method used is qualitative research employing a biblical exegetical approach and lexical study of the New Testament Greek text through literature review. The research findings indicate that the Logos in John 1:1 does not merely mean “the Word,” but points to Jesus Christ as the eternal divine Person, co-existent with God and is God. In John’s Christology, the Logos affirms the pre-existence, divinity, and work of God’s revelation through Christ. This understanding affirms that the Christian faith is centered on Christ as the living Word, the source of truth and salvation, thereby encouraging believers to live in accordance with His truth.